Methylsulfonylmethane ameliorates metabolic-associated fatty liver disease by restoring autophagy flux via AMPK/mTOR/ULK1 signaling pathway - Han, Daewon; Kim, Deokryong; Kim, Haeil; Lee, Jeonga; Lyu, Jungmook; Kim, Jong-Seok; Shin, Jongdae; Kim, Jeong Sig; Kim, Do Kyung; Park, Hwan-Woo (Frontiers in Pharmacology, 2023)
Introduction: Metabolism-associated fatty liver disease (MAFLD) is a global health concern because of its association with obesity, insulin resistance, and other metabolic abnormalities. Methylsulfonylmethane (MSM), an organic sulfur compound found in various plants and animals, exerts antioxidant and anti-inflammatory effects. Here, we aimed to assess the anti-obesity activity and autophagy-related mechanisms of MSM.Method: Human hepatoma (HepG2) cells treated with palmitic acid (PA) were used to examine the effects of MSM on autophagic clearance. To evaluate the anti-obesity effect of MSM, male C57/BL6 mice were fed a high-fat diet (HFD; 60% calories) and administered an oral dose of MSM (200 or 400 mg/kg/day). Moreover, we investigated the AMP-activated protein kinase (AMPK)/mechanistic target of rapamycin complex 1 (mTORC1)/UNC-51-like autophagy-activating kinase 1 (ULK1) signaling pathway to further determine the underlying action mechanism of MSM.Results: MSM treatment significantly mitigated PA-induced protein aggregation in human hepatoma HepG2 cells. Additionally, MSM treatment reversed the PA-induced impairment of autophagic flux. MSM also enhanced the insulin sensitivity and significantly suppressed the HFD-induced obesity and hepatic steatosis in mice. Western blotting revealed that MSM improved ubiquitinated protein clearance in HFD-induced fatty liver. Remarkably, MSM promoted the activation of AMPK and ULK1 and inhibited mTOR activity.Our study suggests that MSM ameliorates hepatic steatosis by enhancing the autophagic flux via an AMPK/mTOR/ULK1-dependent signaling pathway. These findings highlight the therapeutic potential of MSM for obesity-related MAFLD treatment.